2012
DOI: 10.1152/ajpendo.00161.2011
|View full text |Cite
|
Sign up to set email alerts
|

Soymorphin-5, a soy-derived μ-opioid peptide, decreases glucose and triglyceride levels through activating adiponectin and PPARα systems in diabetic KKAy mice

Abstract: Soymorphin-5 (YPFVV) derived from soybean β-conglycinin β-subunit is a μ-opioid agonist peptide having anxiolytic-like activity. Here, we show that soymorphin-5 improves glucose and lipid metabolism after long-term oral administration to KKAy mice, a type 2 diabetes model animal. Soymorphin-5 inhibited hyperglycemia without an increase in plasma insulin levels in KKAy mice. Soymorphin-5 also decreased plasma and liver triglyceride (TG) levels and liver weight, suggesting that soymorphin-5 improved lipid metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 48 publications
0
39
0
9
Order By: Relevance
“…The PPARα-mediated signaling events will particularly promote hepatic fatty acid metabolism and energy expenditure whereas upregulation of SREBP gene would enhance cholesterol metabolism. Similar PPARα-mediated modulation of lipogenic gene expression was reported in diabetic KKAy mice that received soymorphin-5 (YPFVV), a pentapeptide derived from the β-subunit of soybean β-conglycinin [26]. The lipogenic gene regulation induced by soymorphin-5 was associated with hypolipidemic effects including decrease in plasma and liver TG, decrease in liver weight and increase in plasma adiponectin in the diabetic mice [26].…”
Section: Hepatic Functions Of Hypolipidemic Peptidesmentioning
confidence: 72%
“…The PPARα-mediated signaling events will particularly promote hepatic fatty acid metabolism and energy expenditure whereas upregulation of SREBP gene would enhance cholesterol metabolism. Similar PPARα-mediated modulation of lipogenic gene expression was reported in diabetic KKAy mice that received soymorphin-5 (YPFVV), a pentapeptide derived from the β-subunit of soybean β-conglycinin [26]. The lipogenic gene regulation induced by soymorphin-5 was associated with hypolipidemic effects including decrease in plasma and liver TG, decrease in liver weight and increase in plasma adiponectin in the diabetic mice [26].…”
Section: Hepatic Functions Of Hypolipidemic Peptidesmentioning
confidence: 72%
“…A synthetic peptide (molecular weight, 2271) corresponding to the specific sequence of b-conglycinin was also reported to promote the uptake and degradation of LDL in the same cell line (28). Soymorphin-5 (YPFVV) derived from b-conglycinin may lower plasma and liver triglyceride levels via the activation of adiponectin and PPARa pathways in KK-A y mice (18). All the above-mentioned peptides originated from b-conglycinin, which is a major protein fraction of soybean that elicits improvements in triglyceride metabolism (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LD may modulate triglyceride metabolism and contains the component(s) responsible for the hypotriglyceridemic activity of soybean protein. Soybean pentapeptides (18) and oligopeptides (19) have been recently implicated as the components responsible for the triglyceride-lowering effect of soybeans. However, the particular peptides in soybean protein responsible for the triglyceride-lowering effect have not been identified.…”
mentioning
confidence: 99%
“…The studies have shown adverse effects on Vieira et al J Endocrinol Metab. 2017;7(5):135-140 these hormones, having increased levels of adiponectin [37][38][39][40], and decreased levels of leptin [33,35,37,41]. However, there is divergence between these findings, being pointed by some authors the increased circulating leptin and decreased adiponectin [42,43].…”
Section: Soybean and Metabolic Effectsmentioning
confidence: 99%